Provider Preference in Exam Room Layout Design and Computing - Read, Jacob M.; Weiler, Dustin T.; Satterly, Tyler; Soares, Catarina; Saleem, Jason J. (Applied Clinical Informatics, 2019)
Background The introduction of the electronic health record (EHR) has had a significant impact on provider–patient interactions, particularly revolving around patient-centeredness. More research is needed to understand the provider perspective of this interaction.Objectives Our objective was to obtain provider feedback on a new exam room design compared with the one already in use with respect to the computing layout, which included a wall-mounted monitor for ease of (re)-positioning. An additional objective was to understand elements of exam room design and computing that were highly valued.Methods Semistructured interviews were conducted with 28 providers from several health care organizations. Interviews were audio recorded and transcribed for analysis. We used an inductive coding approach to abstract recurrent themes from the data.Results Our analysis revealed several themes organized around exam room layout, exam room computing, and provider workflow. We report frequency of occurrence of the coded data for computer accessories, computing usefulness, computer mobility, documentation habits, form factor, layout preference, patient interaction, screen sharing, and work habits.Conclusion Providers in our study preferred exam room design to promote flexibility, mobility, and body orientation directed toward the patient. Providers also expressed the need for exam room design to support varying work habits and preferences, including whether to share the computer screen or not.
Keywords: human–computer interaction; computer workstations; exam room design; exam room computing; patient centeredness